Numerical Analysis of the Carrying Capacity of a Piled Raft Foundation in Soft Clayey Soils - Danish, Ahmed; Siti Noor Linda, Taib; Tahar, Ayadat; Alsidqi, Hasan (Salehan Institute of Higher Education, 2022)
Piled raft foundations are a common type of foundation for high-rise buildings. Unlike shallow foundations, deep foundations (piles) pass through weak or soft soil deposits and can reach stiff soil or bedrock to support the weight of the structure. In this paper, the performance of a medium embedment depth piled raft foundation in soft soil is presented. A numerical model was developed and a parametric study was conducted in order to simulate the case of such a foundation system and to investigate its performance in soft clay. This parametric study investigated the effect of the geometry of a piled raft foundation and the stiffness ratio between the pile material and clay on the performance of the foundation system in soft soil. Additionally, the failure mechanism of such a foundation system under load was examined. An analytical model was developed to predict the ultimate carrying capacity based on the observed failure mechanism. A semi-empirical model is proposed for determining the Improvement Factor (IF) of a given soil, pile, and geometric condition. Findings of the study indicate that the performance of piled raft foundations on soft soils is significantly affected by the piles’ spacing. As the ratio S/D increases, the ultimate carrying capacity of a piled raft foundation decreases. However, when this ratio exceeds 10 (S/D > 10), piles have little or no effect on the ultimate carrying capacity of this foundation system. A piled raft foundation system fails by bearing at the base of the piles and also by shear at the side of the pile group on hyperbolic plans.